Growth of Pichia guilliermondii strain Levica 27 in different energy sources and nitrogen - Marrero, Yohandra; Montoya, C. A.; Ruiz, O.; Elías, Arabel; Madera, N. (Cuban Journal of Agricultural Science, 2016)
The growth of Pichia guilliermondii yeast Levica 27 strain was studied for its use as microbial additive in ruminant animals. Therefore, yeast growth in NRF medium and malt extract were compared. Then, their development was evaluated when carbohydrates and nitrogen sources varied in the formulation of NRF medium. In sugars, the glucose was substituted by sucrose and lactose and in case of nitrogen the tryptone was substituted by ammonium sulfate, casein and urea. There was not interaction between treatments and the time of study for the count of Levica 27cells in malt extracts and NRF solutions, and there were not differences between both media. In NRF medium, the best growths were achieved when glucose and sucrose were used at 72h and the last one decreased the pH of the medium (P ˂ 0.001).The casein and urea caused higher growth (P ˂ 0.001) after 48h, but urea caused increase of pH. It is concluded that the strain Levica 27 growth was higher before glucose or sucrose, casein or urea. Studies are recommended to design an economical mean of culture with national sources that allows the obtaining of a preparation with Levica 27 with additive effect on ruminants.Key words: Pichia guilliermondii, carbohydrates, nitrogen